Transforming School Environmental Culture through Managerial Leadership of School Principals: A Case Study of SMP Negeri 2 Kajen - Turiyah Turiyah; Harjito Harjito; Nurkolis Nurkolis (AL-ISHLAH: Jurnal Pendidikan, 2025)
Creating an environmentally conscious school culture is essential to advancing education for sustainable development. This study explores how the managerial leadership of the principal at SMP Negeri 2 Kajen transforms school environmental culture within the framework of Indonesia’s Adiwiyata (Green School) Program. A qualitative case study approach was used to examine the principal’s leadership across five managerial functions: planning, organizing, implementing, monitoring, and innovating. Data were collected through in-depth interviews, observations, and document analysis involving school leaders, teachers, and the Adiwiyata team. Thematic analysis was applied using the Miles and Huberman model. The principal played a strategic role in embedding environmental values into the school vision, work plans, and daily routines. Participatory planning involved teachers and the Adiwiyata team, while structured coordination ensured clear task distribution. Implementation included daily waste sorting, Clean Friday routines, school greening, and recycling workshops. Monitoring mechanisms used rubrics and evaluation meetings, while innovations such as digital environmental campaigns and tree adoption fostered student engagement. These practices led to improved environmental behaviors, teacher collaboration, and community involvement. The study demonstrates that effective managerial leadership can institutionalize environmental culture by integrating sustainability into school governance. The findings offer a practical model for schools seeking to align educational leadership with ecological responsibility.